2019
DOI: 10.1038/s41398-019-0422-9
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin G modulation of the melanocortin 4 receptor signaling in obesity and eating disorders

Abstract: Melanocortin 4 receptor (MC4R) plays a key role in regulation of appetite activated by its main ligand α-melanocyte-stimulating hormone (α-MSH) in both central and peripheral targets. α-MSH also binds to circulating immunoglobulins (Igs) but the functional significance of such immune complexes (ICs) in MC4R signaling in normal and pathological conditions of altered appetite has remained unknown. To address this question, we analyzed plasma levels, affinity kinetics, and binding epitopes of α-MSH-reactive IgG e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 50 publications
3
33
0
Order By: Relevance
“…In the present study, we observed no significant difference in the anti-α-MSH IgG concentrations and their affinity among the three groups. This is in agreement with another report from our group comparing anti-MSH IgG concentrations among AN, BN, and BED (DSM-IV) patients [48]. It is worth discussing if some bacterial signaling molecules may contribute to the induction of satiety in a way that is similar to endogenous α-MSH.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we observed no significant difference in the anti-α-MSH IgG concentrations and their affinity among the three groups. This is in agreement with another report from our group comparing anti-MSH IgG concentrations among AN, BN, and BED (DSM-IV) patients [48]. It is worth discussing if some bacterial signaling molecules may contribute to the induction of satiety in a way that is similar to endogenous α-MSH.…”
Section: Discussionsupporting
confidence: 92%
“…In fact, after an increase of ClpB expression during starvation, the immune system in females is already sensitized for the ClpB antigen to raise an adaptive antibody response, as expressed in the increased production of anti-ClpB IgG. While such IgG are not pathogenic themselves, their cross-reactivity with α-MSH may lead to an increased production of immune complexes, with α-MSH overactivating the MC4R and resulting in increased satiety and anxiety of ED patients [9]. In the present study, an increased α-MSH-reactive IgM and IgG response to starvation was found in both sexes, but it was more pronounced in females.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical relevance of α-MSH-reactive immunoglobulin (Ig)M and IgG antibodies to EDs was supported by correlations of their plasma levels with psychopathological traits in both AN and BN patients [8]. The mechanism of action of α-MSH-reactive IgG may include activation of MC4R by the immune complexes with α-MSH, which deregulates feeding behavior and emotions [9].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a recent study showed that the levels of α-MSH-reactive IgG, the binding of melanocortin 4 receptor (MC4R) and the cellular internalization rate of MC4R-expressing cells were all lower in obese subjects [26]. Inverse results were found in anorexic and bulimic patients [26]. Other studies also confirmed the implication of α-MSH reactive Ig in the physiological regulation of feeding and mood [27].…”
Section: Introductionmentioning
confidence: 98%
“…This suggests that α-MSH reactive Ig may interfere with melanocortin signaling in both normal and pathological conditions. Moreover, a recent study showed that the levels of α-MSH-reactive IgG, the binding of melanocortin 4 receptor (MC4R) and the cellular internalization rate of MC4R-expressing cells were all lower in obese subjects [26]. Inverse results were found in anorexic and bulimic patients [26].…”
Section: Introductionmentioning
confidence: 99%